1954
DOI: 10.1002/zaac.19542770307
|View full text |Cite
|
Sign up to set email alerts
|

Über Alkaligraphitverbindungen

Abstract: Durch thermischen Abbau von C8K sowie durch Umsetzung von Graphit mit Kalium und Rubidium konnten weitere Alkaligraphitverbindungen mit Alkalischichten in nur jeder 3., 4. oder 5. basisparallelen Schichtlücke des Graphitgitters erhalten werden. Die Zusammensetzung der 2. Stufe — bisher als C16Me formuliert — entspricht C24Me, die der folgenden Stufen im Idealfall C36Me, C48Me, C60Me. Bei allen Stufen haben die den Alkalischichten benachbarten Kohlenstoffschichten identische Lagen übereinander, während die ande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
1

Year Published

1959
1959
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(72 citation statements)
references
References 5 publications
3
68
0
1
Order By: Relevance
“…They observed the reversible sequence C-KC 36 -KC 24 -KC 8 (Figure 2e,f), indicating that the stage 3, 2, and 1 compounds crystallized in a sequence analogous to the crystallization of the phases prepared by the two-zone vapor method, [31,32] except that the stage 4 and 5 compounds were not detected electrochemically. This discrepancy could originate from the fact that ex situ diffraction was only performed on a limited number of samples (i.e., nonoperando conditions) and it is easy to miss phases that exist in a narrow composition range.…”
Section: Graphite Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed the reversible sequence C-KC 36 -KC 24 -KC 8 (Figure 2e,f), indicating that the stage 3, 2, and 1 compounds crystallized in a sequence analogous to the crystallization of the phases prepared by the two-zone vapor method, [31,32] except that the stage 4 and 5 compounds were not detected electrochemically. This discrepancy could originate from the fact that ex situ diffraction was only performed on a limited number of samples (i.e., nonoperando conditions) and it is easy to miss phases that exist in a narrow composition range.…”
Section: Graphite Anodesmentioning
confidence: 99%
“…[31,32] These compounds were prepared using non-electrochemical methods, through a two-zone vapor transport method, which applies K vapor onto graphite in a custom-made double furnace. Several compounds were isolated in these studies from stage 1 to stage 5 of potassiation, [33] with stage 1 corresponding to the most K-rich compound, KC 8 .…”
Section: Graphite Anodesmentioning
confidence: 99%
“…It was suggested that this difference in 44 reactivity was caused by the fact that the suspensions formed by KC8 in n-pentane and Et2O are not as well dispersed as those formed in THF (Bergbreiter and Killough, 1978). Potassium graphite (commonly referred to as KC8) is the most potassium rich form of a series of graphite intercalation compounds with potassium (Rüdorff and Schulze, 1954). A spacefilling model of KC8 is shown in Figure 10.…”
Section: Reaction Conditions For Reduction Chemistrymentioning
confidence: 99%
“…1 Introduction Graphite intercalation compounds (GICs) have long been the focus of vast research, from which one of the first models presented was KC 8 , a potassium intercalated graphite system introduced by Rüdorff and Schulze in 1954 [1]. Most of the early work was performed using X-ray diffraction (XRD) to determine the structural information on the staging, molecular intercalant structure, layer separation, and in plane densities [2].…”
mentioning
confidence: 99%